(3EOGQI GdefTBJ GdeYGUQI (B/s - (3GdTHdj, gjKe MehOs; (3GdfShQ, eQhGf eMeO s ((3YeGf(B: s (3OGQ UaGA(B, s, 2009)
(3eaGgje EOGQI GdefTBJ GdeYGUQI , JWhQ fXQjGJ JfXje GdefTBJ GdeYGUQI , GdJNWjW GdGSJQGJjLj h GdGOGQI GdGSJQGJjLjI hOhQgeG aj HjFI GdefTCJ GdeYGUQI , EOGQI HjFI GdefTBJ GdeYGUQI , EOGQI GdGMJjGLGJ ef GdehGQO GdHTQjI aj HjFI GdefTBJ GdeYGUQI , EOGQI OhGaY GdYed h MhGaRg h CgejJgG aj JMbjb GdQVG GdhXjaj aj HjFI GdefTBJ GdeYGUQI , EOGQI fXe GdeYdheGJ GdGOGQjI aj HjFI GdefTdBJ GdeYGUQI , GdefTdBJ GdeYGUQI h GdGbJUGO GdeYQaj h EOGQI GdLhOI GdTGedI , GdefXeI GdGaJQGUjI , EOGQI GdLhOI aj HjFI GdefTBJ GdeYGUQI , GdGOGQI GdGdcJQhfjI aj HjFI GdefTBJ GdeYGUQI , EYGOI gfOSI GdYedjGJ aj HjFI GdefTBJ GdeYGUQI , ehGVjY eJNUUUI h JOQjHjI aj EOGQI GdefTBJ GdeYGUQIs
(3HHdjhZQGajG(B: (3U(B.543s
Keywords: (3EOGQI GdGYeGds; (3EOGQI GdGaQGOs; (3GdGOGQIs; (3GdeTQhYGJs